2019
DOI: 10.1021/acs.jpca.9b00908
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur K-Edge X-ray Absorption Spectroscopy of Aryl and Aryl–Alkyl Sulfides

Abstract: Aryl and mixed aryl−alkyl organic sulfides are important species in a variety of fields, including the drug and food industries. They also are present in fossil fuels, where they contribute to the range of sulfur compounds that must be removed by the fuel industry. We have used sulfur K-edge X-ray absorption spectroscopy, in combination with density functional theory calculations, to study the aryl sulfide diphenyl sulfide and two different aryl−alkyl sulfides. The sulfur K near-edge X-ray absorption spectra a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The spectra show a low energy feature marked (*) at about 2470 eV, which increased in intensity upon exposure to the X-ray beam. We interpret this as small amounts of a photo-reduced species, most probably phenylsulde, 51 that accumulated with exposure. agreement with this the feature is most intense in the last spectrum collected (q ¼ 75 ) and shows no intensity in the rst spectra of the series that were collected (q ¼ 90 and 60 ).…”
Section: Single Crystal Polarized X-ray Absorption Near-edge Spectra ...mentioning
confidence: 90%
See 4 more Smart Citations
“…The spectra show a low energy feature marked (*) at about 2470 eV, which increased in intensity upon exposure to the X-ray beam. We interpret this as small amounts of a photo-reduced species, most probably phenylsulde, 51 that accumulated with exposure. agreement with this the feature is most intense in the last spectrum collected (q ¼ 75 ) and shows no intensity in the rst spectra of the series that were collected (q ¼ 90 and 60 ).…”
Section: Single Crystal Polarized X-ray Absorption Near-edge Spectra ...mentioning
confidence: 90%
“…In previous studies of the XAS of compounds in which sulfur is bound to an aromatic ring it has been shown that the spectra can be substantially inuenced by the aromatic ring. 51 For example, the spectrum of diphenylsulde shows a pronounced peak at $1.5 eV above the lower-energy main peak, 51 which is only observed in arylsuldes and not in alkyl or aryl-alkyl suldes. 50,51 Likewise, the aliphatic sulfoxides lack the intense transition 3, suggesting that this involves the aromatic rings.…”
Section: Single Crystal Polarized X-ray Absorption Near-edge Spectra ...mentioning
confidence: 99%
See 3 more Smart Citations